Komodifikasi Budaya Pria Jawa di Iklan Djarum 76 Versi “Om Jin Buat Zaskia Gotik Jatuh Cinta” - Joshua Fernando; Rustono Farady Marta (Ultimacomm: Jurnal Ilmu Komunikasi, 2018)
Djarum 76 is one of the leading cigarette brands in Indonesia and always actively use advertising as a means to promote their products to the public. Ad content that is often used by Djarum 76 is the figure of a light-bulb genie named "Om Jin" which used Javanesse traditional clothing. This study aims to know the commodification of Javanese men in the family which was portrayed in the figure of "Om Jin" in one of Djarum 76 ad versions titled "Om Jin Makes Zaskia Gotik Fall in Love - Glorious Kingdom MNCTV 25". This research looks at how the construction of meaning occurs using Barthes semiotics and analyzes the data with Hofstede’s Cultural Dimension. This research uses dialectical cross-cultural communication paradigm which integrates interpretive and critical paradigm with qualitative approach providing descriptive data. The result shows shifting of meaning in the process of cultural commodification of Javanese man character in Djarum advertisement. Keywords: Advertising, culture, semiotics, Javanese Men, commodification